Efficacy of Friedland clay (montmorillonite–illite mixed layer clay) when used as a technological additive for all animal species - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (EFSA Journal, 2015)
Abstract Friedland clay (montmorillonite–illite mixed layer clay mineral) was shown to be effective as a binder (at concentrations between 1 and 2 % in four different types of feed) and as an anticaking agent (at concentrations of 2 % in rolled oats, in a mixture of poultry grains and a high fat compound feed). It was concluded that Friedland clay has the potential to act as a binder and as an anticaking agent in feed for all animal species.